Literature Review: Improving the Writing Ability of Grade 2 Elementary School Students Using Word Cards - Lestari, Dwi Setyo Muji; Hendratno, Hendratno; Subrata, Heru (International Journal of Emerging Research and Review, 2024)
Objectives: This research reviews the literature on using word card media to improve the writing skills of grade 2 elementary school students. Method: The research method is a literature review of articles and journals on Google Scholar between 2014 - 2023, totalling 10 articles discussing writing skills and 8 articles about word card media. Data analysis uses qualitative descriptive methods. Results: The focus of the research is the effectiveness of using word card media in improving students' writing skills. Studies show that word card media has advantages in terms of ease of use and is effective in attracting students' learning habits so that students' ability and creativity in writing increases. Novelty: The novelty of this research is that the literature review used comes from Google Scholar, so the results of the review can provide information on the level of success in using word card media to improve students' writing skills. This research focuses on how effective word card media is in improving the writing skills of grade 2 elementary school students.